Angiotensin-converting enzyme 2 expression is not induced by the renin–angiotensin system in the lung. Issue 4 (5th October 2020) - Baba, Ryuta; Oki, Kenji; Itcho, Kiyotaka; Kobuke, Kazuhiro; Nagano, Gaku; Ohno, Haruya; Yoneda, Masayasu; Hattori, Noboru
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has developed into a pandemic with significant morbidity and mortality. SARS-CoV-2 has been reported to invade lung epithelium via the angiotensin-converting enzyme 2 (ACE2) receptor using its glycosylated cell surface spike protein [1]. ACE2 expression in the heart and kidney is regulated by the renin–angiotensin system (RAS), especially angiotensin II (A-II), which is catalysed from angiotensin I (A-I) by angiotensin-converting enzyme (ACE) [2]. In a cohort study in the early period of the COVID-19 outbreak in Wuhan in China, hypertension was found in 30% of the patients and was identified as the most common comorbidity [3]. It has recently been reported that RAS inhibitors are not associated with the severity of COVID-19 in a meta-analysis that included nine studies comprising 3936 patients with hypertension and COVID-19 [4]. The most serious concerns for the use of RAS inhibitors may be related to their role in development of or exacerbation of COVID-19, as suggested in a recent review by Ingraham et al . [5]. However, the alteration in ACE2 expression in pulmonary cells has not been studied. Pulmonary expression of angiotensin-converting enzyme 2, which is a receptor of severe acute respiratory syndrome coronavirus 2, is not regulated by angiotensin II or renin–angiotensin system inhibitors #COVID19 https://bit.ly/3fkopuO